Percutaneous Sclerotherapy of Cystic Lesions - Cheng, Danny; Amin, Parag; Van Ha, Thuong (Seminars in Interventional Radiology, 2012)
With modern cross-sectional imaging techniques, cystic lesions are very common and usually incidental findings, especially if small. However, when cysts enlarge, become infected, bleed, or undergo torsion, they can be symptomatic, and percutaneous drainage can be effective in the management. When cysts recur after aspiration, which is often the case for hepatic and renal cysts, cyst sclerosis or surgical unroofing may be required. This article describes the indications for and technical aspects of percutaneous sclerotherapy of cystic lesions of multiple organ systems.
Keywords: interventional radiology; sclerotherapy; cysts; alcohol